The importance of combining MRI and large-scale digital histology in neuroimaging studies of brain connectivity and disease - Annese, Jacopo (Frontiers in Neuroinformatics, 2012)
One of the major issues hindering a comprehensive connectivity model for the human brain is the difficulty in linking Magnetic Resonance Imaging (MRI) to anatomical evidence produced by histological methods. Non-invasive and postmortem neuroimaging methodologies are still largely incompatible in terms of sample size, scale, and resolution. To help bridge the hiatus between different approaches we established a program that characterizes the brain of individual subjects, combining in vivo MRI with postmortem neuroanatomy. The direct correlation of MRI and histological features is possible, because registered images from different modalities represent the same regions in the same brain. Our comparisons are also facilitated by large-scale, digital microscopy techniques that afford images of the whole-brain sections at cellular resolution. The goal is to create a neuroimaging catalogue representative of discrete age groups and specific neurological conditions. Individually, the datasets allow for investigating the relationship between different modalities; combined, they provide sufficient predictive power to inform analyses and interpretations made in the context of exclusively non-invasive studies of brain connectivity and disease.